The Beginning and Evolution of Punjabi Short Story in "The Ravi" Magazine - Latif, Wasif; Sadiq Wattoo, Subah (sourcecoder, 2022)
Government College, Lahore's magazine "The Ravi" has been published continuously since July, 1906, in which English, Urdu and Hindi as well as Punjabi Shahmukhi and Gurmukhi poetry and prose literature have been published in significant quantities. Along with Punjabi poetic genres, Punjabi prose genres also adorn the pages of "The Ravi" which includes articles, fiction, short stories, plays, editorials and satire and humor. Short Stories in "The Ravi" begins with Sher Singh Giani's Gurmukhi short story "MaaN tay Puttar", the first part of which was published in April 1925 and the second part in May, June 1925. This research article reviews the beginnings and evolution of Punjabi short stories published in "The Ravi".